HUBUNGAN INDEKS MASSA TUBUH DENGAN STATUS ANEMIA PADA REMAJA PUTRI - Putu Uci Paramudita; Ni Made Dwi Mahayati; Ni Ketut Somoyani (Poltekkes Kemenkes Denpasar, 2021)
Monitoring the state of adolescent hemoglobin is one of a woman's preparations for pregnancy, it is expected to be able to suppress AKI as a result of bleeding in labor. In general, the purpose of this study was to determine the relationship between body mass index and anemia status in adolescent girls in PGRI Dawan Klungkung Tourism High School. This research is a correlational analytic study with cross sectional design. The sampling technique uses Proportional Random Sampling technique. The data collected is primary data (via Google form) and secondary data (puskesmas documentation data). Bivariate analysis with the Fisher Exact Test showed BMI was not related to anemia status with a p-value = 0.708 (p 0.05). The conclusion of this study there is no relationship between BMI and anemia status in young women in PGRI Dawan Klungkung Tourism High School. It is recommended for further researchers to develop research with different variables such as other factors that can affect anemia.